Case report: A multiple sclerosis patient with imaging features of glymphatic failure benefitted from CSF flow shunting - Scollato, Antonio; Lolli, Francesco; Lastrucci, Giancarlo; Repice, Anna; De Santis, Giuseppe; Nicoletti, Claudio; Porfirio, Berardino; Gallina, Pasquale (Frontiers in Neuroscience, 2022)
The derangement of CSF circulation impacts the functions of glymphatic-lymphatic system (G-Ls), which regulates solute trafficking and immune surveillance in the CNS. The G-Ls failure leads to dysregulation of waste molecules clearance in the brain and to an altered CNS immune response. The imaging features of dilated perivascular spaces imply the impairment of the G-Ls. We report on the case of a patient with primary progressive multiple sclerosis and dilatation of perivascular spaces, who transiently improved after CSF shunt diversions. The underling mechanisms remain to be determined and at this stage it is not possible to link CSF diversion to an effect on the MS pathology. However, this observation provides the rationale to incentivize research in the largely unknown area of CSF dynamic disturbances on G-Ls failure and ultimately in neurodegeneration.